(1) 3a^3+6a^2+3a (2)x^2(x-y)+9(y-x) (3)(x^2+4)^2-16x^2 因式分解

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/16 21:07:48
(1) 3a^3+6a^2+3a (2)x^2(x-y)+9(y-x) (3)(x^2+4)^2-16x^2 因式分解
xPK 0J@G(MJs@<ݤPp%z^Mյn¼yM=]2G")A($GRK|;Z y2MI$h,TrdL6]ĸ?jHVy BukI2tJ{AVY}V@Y0yP!0~ s3K

(1) 3a^3+6a^2+3a (2)x^2(x-y)+9(y-x) (3)(x^2+4)^2-16x^2 因式分解
(1) 3a^3+6a^2+3a (2)x^2(x-y)+9(y-x) (3)(x^2+4)^2-16x^2 因式分解

(1) 3a^3+6a^2+3a (2)x^2(x-y)+9(y-x) (3)(x^2+4)^2-16x^2 因式分解
(1)3a³+6a²+3a=3a(a²+2a+1)=3a(a+1)²
(2)原式=x²(x-y)-9(x-y)=(x-y)(x²-9)=(x-y)(x+3)(x-3)
(3)原式=(x²+4)²-(4x)²=(x²+4+4x)(x²+4-4x)=(x+2)²(x-2)²